Religion and covenantal praxis in first century Judeanism - Cromhout, Markus (HTS teologiese studies, 2007)
This article indicates how the two cultural features of religion and covenantal praxis helped foster or shape Judean ethnic identity in the first century CE. It focuses on socialization into the three social domains of the Temple, the synagogue and the home. In these domains, Judean ethnic identity was dominated by the requirements of the Torah. At the same time the presence of Romans, the Herodians and the Gentiles within the ancestral land helped shape Judean identity as well.